Pelatihan Pengembangan Media Pembelajaran Digital Storytelling Berbasis Pendekatan Billingual dengan Software Articulate Storyline Bagi Guru SD di Kabupaten Sleman - Banun Havifah Cahyo Khosiyono; Sukiyanto Sukiyanto; Dinar Martia Azizah; Hutri Darmayanti; Ana Ika Ariyani; Kurnia Nurvina Laila Alifah; Diah Kartika (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
This training activity aims to resolve existing problems among partners in order to support efforts to address the limited competencies of the Kapnewon Ngemplak Elementary School Teacher Learning Community in developing bilingual digital storytelling. The objectives of this training program were to: (1) introduce the concept of a bilingual approach at the elementary school level; (2) introduce the digitalization of learning media; and (3) provide assistance in the development of bilingual-based digital storytelling using the Articulate Storyline software. The community service activity was carried out through a training program provided to teachers from 27 elementary schools in Kapanewon Ngemplak, Sleman, Special Region of Yogyakarta. The training was delivered in three sessions. The results of the training showed that: (1) the teachers gained an understanding of the bilingual approach concept for elementary education; (2) the teachers developed an awareness of the importance of developing digital learning media; and (3) the teachers were able to create bilingual-based digital storytelling media using Articulate Storyline software. It can be concluded that the training program has equipped teachers with the skills to integrate technology into more meaningful elementary school learning, in line with the demands of 21st-century education. This supports the enhancement of teacher competence and curriculum adaptation in the era of the Industrial Revolution 4.0. As a recommendation, the media developed during the training can be implemented in the classroom and followed up with lesson study activities involving other training participants.